PENGARUH PENGGUNAAN METODE OPEN WINDROW DAN TAKAKURA TERHADAP PENGOMPOSAN DEDAUNAN KERING - Budi Nining Widarti (Universitas Lambung Mangkurat, 2018)
Garbage of yard has the highest composition of dry foliage. Dried foliage has potensial organic content to be composed. Simple composting is by using natural aeration that can be done by open windrow and takakura method. This studi aims to determmine the optimal method to produce compost with hight quality. This researsch was done variation of dry composting method using open windrow and takakura method. The result of this study shows that open windrow and takakura method of composting gave no effect to the ratio of C/N, N, P and K on composting dry foliage, so it can be concluded the use of natural aeration used in these two methods did not give a different effect on the ratio of C/N, N, P and K on the composting of dry foliage.